The consequences of managerial indiscretions: Sex, lies, and firm value - Cline, Brandon N.; Walkling, Ralph A.; Yore, Adam S. (Journal of Financial Economics, 2018)
Personal managerial indiscretions are separate from a firm's business activities but provide information about the manager's integrity. Consequently, they could affect counterparties’ trust in the firm and the firm's value and operations. We find that companies of accused executives experience significant wealth deterioration, reduced operating margins, and lost business partners. Indiscretions are also associated with an increased probability of unrelated shareholder-initiated lawsuits, Department of Justice and Securities and Exchange Commission investigations, and managed earnings. Further, chief executive officers and boards face labor market consequences, including forced turnover, pay cuts, and lower shareholder votes at re-election. Indiscretions occur more often at poorly governed firms where disciplinary turnover is less likely.